“We won this war...” Unrecorded confession of Mendel Khataevich - Marochko, Vasyl (Ukrainian Peasant, 2024)
The purpose of the article is to establish the historical authenticity of the events and phenomena highlighted in the memoirs of the Soviet emigrant-fugitive Viktor Kravchenko — «I chose freedom». The scientific noveltyof the research results lies in the scientific and historical interpretation of the key points of the memoir edition. They refer to the assessment judgments of a Party-Soviet official about the Holodomor. The object of the study is the statement of Stalin’s envoy to Ukraine, Mendel Khataevich, who recognized the artificial famine in Ukraine as a war against the peasants. The subject is the verification of the content of key quotations, their factual content, and the establishment of historical authenticity.A comparison of public speeches and official correspondence of the party leader with their retrospective reproduction in the mentioned book proves a logical connection between them. The methodology is determined by the formulation of the problem, so specific methods of historical and archeographic research were used. Textological analysis required the use of the historical-comparative method, fragmentation of the work according to the chronology of events. Reconciling the personal and political life of a Soviet government official necessitated the use of a universal biographical method. Author’s conclusions. Memoirs, memories of eyewitnesses are an important source of «oral history». Western researchers cited the mentioned book and the circumstances of its author’s escape to the United States. No one denied his assessments, did not question the authenticity of the events. Western historiography relied on the memoirs of ex-Soviet figures who emigrated. It is noted that Khataevich’s official speeches correspond to the «word and spirit» of his «off-the-record» confessions recorded in Kravchenko’s memoirs. The compilers of the 2022 Ukrainian-language edition of the work also confirmed the authenticity of the text, but without its historical verification by comparing materials.